SIMULASI SKEMA MODULASI 1024-QAM DAN 4096-QAM PADA SISTEM KOMUNIKASI DIGITAL - Danang Maulana Ikhsan; Theophilus Wellem (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Quadrature amplitude modulation (QAM) is a modulation scheme used by digital communication systems to obtain high data rates in bandwidth-limited channels. M-ary QAM schemes with M values greater than 256 are currently used by wireless network standards, such as WiFi 6 and WiFi 7 (final standard will be released in 2024), which use the 1024-QAM and 4096-QAM modulation schemes, respectively. With the continuous development of technology for digital communication systems, both wireline and wireless, it is essential to research regarding advanced modulation schemes. This study discusses the simulation of the 1024-QAM and 4096-QAM modulation schemes using MATLAB software to compare the performance of the two modulation schemes in data transmission through the AWGN channel without using an error control code. The simulation results show that 4096-QAM is superior to 1024-QAM but requires higher Eb/N0 and SNR values. The Eb/N0 value required by the 4096-QAM to achieve a bit error ratio (BER) of 10-4 is 31 dB, while the 1024-QAM requires an Eb/N0 value of 26 dB.